Комплексный подход к оценке уровня освоения студентами запланированных компетенций - Похолков Ю. П. Юрий Петрович; Муравлев И. О. Игорь Олегович; Жадан В. А. Валерий Афанасьевич; Корнева О. Ю. Ольга Юрьевна; Червач М. Ю. Мария Юрьевна; Климова Г. Н. Галина Николаевна; Леонова Л. А. Лилия Александровна; Максимова Ю. А. Юлия Анатольевна; Першина А. А. Анна Александровна; Савинова О. В. Олеся Вячеславовна; Степанов С. А. Сергей Александрович (2022, 2022)
Заглавие с титульного листа